X-ray Imaging of Stored Dates to Detect Infestation by Saw-Toothed Beetles. Issue 1 (2nd January 2016) - Al-Mezeini, Nawal; Manickavasagan, Annamalai; Al-Yahyai, Rashid; Al-Wahaibi, Ali Khalfan; Al-Raeesi, Ali Ahmed; Khriji, Lazhar
ABSTRACT: The objective of this study was to investigate the capability of X-ray imaging in detecting internal infestations caused by the saw-toothed beetle ( Oryzaephilus surinamensis L. ) in stored dates. Un-infested and infested dates were x-rayed for different life stages (egg, larvae, pupae, and adult) of O. surinamensis . An algorithm was developed to extract 44 features from the X-ray images. Linear discriminant analysis (LDA) was used to discriminate the un-infested and infested dates using extracted features. Overall accuracy of X-ray imaging system was 80% for un-infested and beetle-infested dates. X-ray imaging system yielded around 97% accuracy in detecting internal infestation of dates with an adult beetle while using a pairwise classification method. Further studies are required to investigate the effects of moisture content and hardness of dates in the discrimination between the un-infested and infested dates.